Penerapan Sistem Informasi Akuntansi untuk Meningkatkan Penjualan pada UD. Cahaya Goa Mampu - B, Muslimin; Riza Putra, Emil; Bin Idris, Nasruddin; Jamal, Jamal (LPPM Universitas Mulia, 2025)
Cahaya Gowa Mampu is a Micro, Small, and Medium Enterprise (MSME) engaged in the sale of agricultural products and the rental of farming equipment, located in Sekaduyan Taka Village, Nunukan City. This study aims to improve sales transaction management, accurate stock inventory recording, agricultural equipment rentals, and transparent financial reporting. The research employs the waterfall methodology, including interviews and data analysis on sales transactions, stock management, and equipment rentals. The findings indicate that implementing an accounting information system at UD. Cahaya Gowa Mampu enhances recording accuracy, reduces transaction time, improves sales transparency, optimizes inventory and rental management, and increases monthly sales and equipment rental summaries. The adoption of digital information technology through an accounting information system enhances operational efficiency, improves customer service, and enables real-time monitoring of periodic financial reports.